A Quick Survey on the Application of Augmented Reality in Education - Rizdania Dermawi; Sapto Hadi Riono; Dimas Rega Hadiatulloh (JITeCS (Journal of Information Technology and Computer Science))
Current conditions, especially the Covid-19 pandemic, force us to conduct online education. However, its implementation must be considered carefully to avoid becoming boring. The use of exciting technologies such as augmented reality can be an option. This scientific paper is a short review of the last ten years of studying AR technology in various fields of education. The evaluation of these previous studies shows that AR is a technology with great potential to be applied in education. However, the survey also demonstrates the limits of AR, which could be tended to in future research.